The Effect of Self-Regulation on the Need for Psychological Help Through Happiness, Resilience, Problem Solving, Self-Efficacy, and Adjustment: A Parallel Mediation Study in Adolescent Groups - İhsan Akeren; Eyüp Çelik; İbrahim Erdoğan Yayla; Mustafa Özgöl (Children)
Introduction: Adolescence is a developmental period in which the risk of mental problems is high. Failure to resolve the problems encountered during this period may result in the need for psychological help. Based on the literature review, this study aimed to examine self-regulation, which has the potential to reduce adolescents’ need for psychological help, and the mediation of happiness, resilience, problem solving, self-efficacy, and adjustment through this skill. Methods: In the cross-sectional correlational survey design study, 1013 adolescents (542 girls, 471 boys, mean age: 15.04 ± 1.75 years) aged 12–19 years and studying in middle and high school in Bayburt, Turkey were reached. Seven different questionnaires, valid and reliable in adolescent groups, were used to measure the study variables. Results: Correlation results showed that all predictors were positively correlated with each other and negatively correlated with the dependent variable, the need for psychological help. After testing the assumptions, the results of the parallel mediation analysis showed that happiness, problem solving, self-efficacy, and adjustment fully mediated the effect of self-regulation on the need for psychological help. Another finding is that resilience is not a predictor of psychological distress. Conclusions: The results are important because they provide insight for those working in the field of adolescent mental health in terms of understanding the factors through which self-regulation reduces the need for psychological help.